Improvement of aerodynamic analysis on helicopter rotor blade by applying passive flow control / Mohd Hafiz Mohd Noh, Ahmad Hussein Abdul Hamid and Muhammad Shahrul Azryn Hanif - Mohd Noh, Mohd Hafiz; Abdul Hamid, Ahmad Hussein; Hanif, Muhammad Shahrul Azryn Hanif (Smart Manufacturing Research Institute (SMRI), 2025)
Rotor blades are essential for helicopter flight as they provide lift similar to an airplane’s wings, allowing the aircraft to take off, hover, and maneuver. However, they also generate aerodynamic drag, which can reduce maximum speed, stability, maneuverability, and fuel efficiency. The enhancement on the blade is usually done at the trailing edge area; however, this time it was done at the leading edge location. This study explored the use of passive flow control to enhance rotor blade performance by minimizing surface turbulence. Through Computational Fluid Dynamics (CFD) analysis, key parameters such as velocity and lift-to-drag ratios coefficient are examined at a Reynolds number (Re) of 3×10⁶. The research utilized the SST k-ω turbulence model and an unstructured mesh to simulate airflow around a NACA 0012 airfoil at a 15° angle of attack. Passive flow control was applied using slots of 5%, 10%, and 15% of the chord length, placed in turbulent flow regions and extending downstream. The findings indicate that positioning passive flow control further downstream increases the lift-todrag ratio with 5% slot sizes delaying turbulence, improving velocity reattachment to the blade surface and improving the lift-to-drag ratio by approximately 77% compared with non slot blade. This highlights the effectiveness of passive flow control in improving the aerodynamic efficiency of rotor blades.